A stylistic comparison of selected visual representations on Egyptian funerary papyri of the 21st Dynasty and wooden funerary stelae of the 22nd Dynasty (c. 1069 -715 B. C. E.) - Swart, Lisa (Stellenbosch : Stellenbosch University, 2012)
Thesis (DPhil)--Stellenbosch University, 2004.